Connecting land tenure to climate change - Chigbu, Uchendu Eugene (Land use policy, 2025)
Despite its pivotal role in shaping global climate change policies, the United Nations Framework Convention on Climate Change (UNFCCC) has not entirely put land tenure at the centre of its climate change efforts. We used this scientific viewpoint to situate climate change as an inter-, intra-, trans-, cross-, multi-disciplinary and multi-sectoral subject. We methodologically framed our argument on a positionality statement that used desktop and Artificial intelligence investigations to show that no UNFCCC decisions or resolutions have explicitly focused on land tenure. On this basis, we sought to establish the connection between land tenure and climate change to encourage the UNFCCC and other stakeholders engaged in the climate change discourse to make land tenure a Centrepoint of the climate change effort. To argue that land tenure and climate change are related, we illustrated the role and importance of land tenure in climate change. Finally, we concluded that since land tenure and climate change are connected, the success of climate actions depends on land tenure. •Of 977 decisions identified on the UNFCCC website, 24 are on land use, and none are on land tenure.•Land issues are linked to climate change through land tenure.•The connections between land tenure and climate change are conceptual and experiential.•Land tenure measures ensure that climate solutions are locally owned, culturally appropriate, and procedurally enduring.